2018
DOI: 10.1111/pbr.12672
|View full text |Cite
|
Sign up to set email alerts
|

The role of ear environment in postharvest susceptibility of maize to toxigenic Aspergillus flavus

Abstract: A kernel screening assay (KSA) was used to assess the genetic and environmental effects on the vulnerability of maize to aflatoxin accumulation. Kernels of 26 inbred lines that had been grown in seven environments, and 190 lines of the Intermated B73xMo17 (IBM) population grown in one location in the United States, were inoculated with a toxigenic strain of A. flavus and incubated in the dark at 30°C for 6 days. Percent kernel colonization (PKC), sporulation and aflatoxin were influenced by the maize genotypes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…It has also been observed that specific farming methods, such as rotation with specific crop species (e.g., soybean) could reduce the occurrence of Fusarium and trichothecenes in wheat [ 69 ]. It has also been argued that kernel chemical composition, which is influenced by soil nutritional content, can affect the susceptibility of cereals to mycotoxins [ 70 ]. Besides soil and climatic conditions, multiple localized or region-based preharvest agronomic practices could influence the occurrence of mycotoxigenic fungi.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been observed that specific farming methods, such as rotation with specific crop species (e.g., soybean) could reduce the occurrence of Fusarium and trichothecenes in wheat [ 69 ]. It has also been argued that kernel chemical composition, which is influenced by soil nutritional content, can affect the susceptibility of cereals to mycotoxins [ 70 ]. Besides soil and climatic conditions, multiple localized or region-based preharvest agronomic practices could influence the occurrence of mycotoxigenic fungi.…”
Section: Discussionmentioning
confidence: 99%
“… Intrinsic crop characteristics: A crop’s inherent properties like nutritional content, pH, and genetic makeup also play a crucial role. Cultivating crops adapted to their specific environmental conditions can enhance their resistance to fungal spoilage [ 85 ]. …”
Section: Prevalence Of Mycotoxins In Food and Feedmentioning
confidence: 99%
“…Maize crops are very susceptible to fungal attacks, both in the field and during storage (Mutiga et al, 2019). Depending on environmental conditions, a fungal infection might be mainly produced by species of Aspergillus (Sserumaga et al, 2020), Fusarium (Castañares et al, 2019) and Penicillium (Ekwomadu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%